Repeated Application of a Novel Creatine Cream Improves Muscular Peak and Average Power in Male Subjects. Issue 9 (September 2020) - Whinton, Alanna K.; Donahoe, Katelynn; Gao, Ruirui; Thompson, Kyle M.A.; Aubry, Rachel; Saunders, Travis J.; Johnston, Adam; Chilibeck, Philip D.; Burr, Jamie F.
Abstract : Abstract: Whinton, AK, Donahoe, K, Gao, R, Thompson, KMA, Aubry, R, Saunders, TJ, Johnston, A, Chilibeck, PD, and Burr, JF. Repeated application of a novel creatine cream improves muscular peak and average power in male subjects. J Strength Cond Res 34(9): 2482–2491, 2020—Using a multicenter, randomized controlled trial, ( N = 123, age 23 ± 4 years) we sought to determine whether administration of a novel, topical creatine supplement could improve muscular performance after acute and repeated (7-day) exposure. To study the acute performance enhancing effects of the supplement, subjects completed 5 sets of 15 maximal concentric single-leg knee extensions with and without the application of a low- (low dose [LD]-3.5 ml) or high-dose (high dose [HD]-7 ml) topical creatine cream. After a wash-out period, subjects had one leg randomized to receive either the creatine or placebo cream, with further randomization into an oral creatine or placebo supplement group. Subjects completed 5 sets of 15 maximal concentric single leg knee extensions before and after the supplementation protocol. After acute application, no significant differences in peak power (LD: 252 ± 93 W, HD: 261 ± 100 W, p = 0.21), average power (LD: 172 ± 65 W, HD: 177 ± 69 W, p = 0.78), or fatigue index (LD: 13.4 ± 10.6%, HD: 14 ± 11.9%, p = 0.79) were observed between experimental and placebo creams (peak power: LD: 244 ± 76 W, HD: 267 ± 109 W; average power: LD: 168 ± 57 W, HD: 177 ± 67 W; fatigue index: LD: 12.4 ± 9.6%, HD: 12.8 ± 10.6%) or when controlling for sex. After the 7-day supplementation protocol, a significant increase in average power (creatine: 203 ± 61–220 ± 65 W, placebo: 224 ± 61–214 ± 61 W) and peak power (creatine: 264 ± 73–281 ± 80 W, placebo: 286 ± 79–271 ± 73 W) in the leg receiving creatine cream was observed in male subjects. No differences were observed in female subjects. The topical creatine cream did not enhance measures of muscle performance after acute application, but was able to improve peak and average power in male subjects after 7 consecutive days of application. Abstract : Supplemental Digital Content is Available in the Text.